Las diásporas de los árboles y arbustos nativos de México: posibilidades y limitaciones de uso en programas de reforestación y desarrollo agroforestal - Niembro Rocas, Aníbal (Instituto de Ecología, A.C., 2016)
The importance of the diaspores of the trees and native shrubs of Mexico like materials of propagation of plants with reforestation ends and agroforestry development is analyzed, highlighting the causes that have limited the use this form of germplasm in forest nurseries. It is concluded the how necessary is to strengthen research on phenology, structure and diaspore morphology, dormancy and viability, germination and initial development of seedlings for those species potentially important of the nine thousand growing in the national territory.